Evaluation of the Use of Intrinsic Religiosity as Moderating Variable on the Effect of Self-Assessment System, Gender, and the Period as Taxpayer toward Tax Evasion - Maulia Regita Belananda; Rusmawan Wahyu Anggoro (Journal of International Conference Proceedings (JICP), 2022)
The importance of this research was due to the greater dependence on the government budget (APBN) sourced from taxes. Tax avoidance is an action that has a negative effect on state revenues became a major concern for most countries to mitigate. This study aimed to evaluate the moderating role of intrinsic religiosity on the effect of the self-assessment system, gender, and the period as a taxpayer toward tax evasion.  Evaluation of factors that can minimize tax avoidance, such as religiosity, is expected to provide important information for the tax authorities to optimize tax revenue. The purposive sampling method was used to select a sample of taxpayers. The research data and hypothesis were analyzed and tested using moderated regression analysis (MRA). The results of this study indicate that the self-assessment system has a negative effect on tax evasion. While gender and the period as the taxpayer has no significant effect on tax evasion, and this study failed to support intrinsic religiosity as a moderating variable toward tax evasion.